Acute Pancreatitis, Actualization and Evidence Based Management - Luis Angel Medina Andrade; Arsenio Torres Delgado; Luis Fernando Perez Corona; Oscar Sanchez Moreno; Daniel Flores Rodríguez; Oscar Rodrigo Rocha Erazo; Eduardo Vidrio Duarte; José Daen Jonathan Cabañas Gomez; Rene Cano Rodriguez; Nestor Apaez Araujo; Oscar Arturo Nava Carmona (Archives of Clinical Gastroenterology - Peertechz Publications, 2017)
Acute pancreatitis (AP) is a systemic immunoinfl ammatory response to auto-digestion of the pancreas and peri-pancreatic organs. It is a frequent gastrointestinal disease with an important morbimortality, reaching 30% in severe cases. Different studies and reviews by international groups have developed multiple classifi cation systems to assess the severity and address the correct management along time, identifying the better molecular markers, clinical outcome determinants and reaching conservative management as the angular piece in AP. In this review we present a compilation of the latest studies and international consensus about AP physiology, etiology, risk factors, diagnosis, severity assessment, imaging and treatment.